2003
DOI: 10.1177/1073858402239587
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines: Powerful Regulators of Glial Cell Activation

Abstract: It is now clear that cytokines function as powerful regulators of glial cell function in the central nervous system (CNS), either inhibiting or promoting their contribution to CNS pathology. Although these interactions are complex, the availability of animals with targeted deletions of these genes and/or their receptors, as well as transgenic mice in which cytokine expression has been targeted to specific cell types, and the availability of purified populations of glia that can be studied in vitro, has provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
210
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(221 citation statements)
references
References 91 publications
7
210
0
4
Order By: Relevance
“…Microglia and astrocytes can, by an NF-kB-mediated mechanism, produce large amounts of proinflammatory cytokines, reactive oxygen species, and excitotoxins. 68 NF-kB can also induce nitric oxide synthase in glial cells resulting in the production of nitric oxide and related neurotoxic reactive oxygen species. 69 A recent study in which irradiated wild-type mice were transplanted with bone marrow from mice lacking inducible nitric oxide synthase provided evidence for an important role for glial nitric oxide in excitotoxin-induced neuronal death.…”
Section: Nf-jb As a Regulator Of Cell Survivalmentioning
confidence: 99%
“…Microglia and astrocytes can, by an NF-kB-mediated mechanism, produce large amounts of proinflammatory cytokines, reactive oxygen species, and excitotoxins. 68 NF-kB can also induce nitric oxide synthase in glial cells resulting in the production of nitric oxide and related neurotoxic reactive oxygen species. 69 A recent study in which irradiated wild-type mice were transplanted with bone marrow from mice lacking inducible nitric oxide synthase provided evidence for an important role for glial nitric oxide in excitotoxin-induced neuronal death.…”
Section: Nf-jb As a Regulator Of Cell Survivalmentioning
confidence: 99%
“…More recently however it has been suggested that cytokine activated astrocytes also promote the recovery and repair of CNS function by producing trophic factors for neurons and oligodendrocytes, acting as free radical and excess glutamate scavengers, actively restoring the blood -brain barrier, promoting neovascularization, restoring CNS ionic homeostasis, promoting remyelination and stimulating neurogenesis from neural stem cells (John et al, 2003;Liberto et al, 2004). These studies indicate that astrocytes have important and variable roles in the immune response in the CNS infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although activation of NF-kB in neurons is often protective, its activation in microglia tends to promote neuronal apoptosis, perhaps due to the production of proinflammatory cytokines, reactive oxygen species (ROS) and excitotoxins (John et al, 2003;Mattson and Meffert, 2006). Supporting the idea that NF-kB's well-documented role in inflammation can foster central nervous system (CNS) injury following trauma, targeted inhibition of NF-kB in astroglial cells by tissue-specific expression of the IkBa super-repressor noticeably ameliorated recovery of mice following spinal cord injury and this effect coincided with a reduced production of proinflammatory cytokines (Brambilla et al, 2005).…”
Section: Introductionmentioning
confidence: 99%